Analysis of Factors Influencing the Lack of Literacy Skills of Class III Students at SDI AL-FURQON Academic Year 2024/2025 - Rahayu, Fitriani; Nasir, Muhammad Dahrun; Ahdiawati, Denda Nila; Nopiana, Rizka; Aryantika, Denda Sapti; Minawati, Minawati; Paoziah, Zahratun; Wahyuni, Diana; Suparman, Muh (Jurnal Ilmiah Mandala Education (JIME), 2024)
This service aims to describe the analysis of factors that influence the lack of reading ability of low-grade students. This service was carried out at SDI Al-Furqon, Lendang Berora Hamlet, Sigar Penjalin Village, Tanjung District, North Lombok Regency. What is the object of this problem are the factors that cause the lack of reading ability of lower-class students in Class III Elementary School students, where their age is around 9-10 years, namely the transition period after toddlerhood to childhood. Age in this research is what causes low reading ability in class III